2016
DOI: 10.1093/gbe/evw149
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Evolution of Snake Toxins Underscored by an Integrative Omics Approach to Profile the Venom of the ColubridPhalotris mertensi

Abstract: Only few studies on snake venoms were dedicated to deeply characterize the toxin secretion of animals from the Colubridae family, despite the fact that they represent the majority of snake diversity. As a consequence, some evolutionary trends observed in venom proteins that underpinned the evolutionary histories of snake toxins were based on data from a minor parcel of the clade. Here, we investigated the proteins of the totally unknown venom from Phalotris mertensi (Dipsadinae subfamily), in order to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…The use of deep-sequencing technologies as RNA-seq have allowed the identification and quantification of bioactive compounds of biotechnological importance [5]. Nonetheless, only a limited number of transcriptomes from sea anemones have been sequenced so far [6], [7], [8], [9], [10], [11] Here we performed de novo transcriptome assembly for the sea anemone Anthopleura dowii Verrill (1869) (Actiniaria: Enthemonae: Actinioidea: Actiniidae) by next-generation sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…The use of deep-sequencing technologies as RNA-seq have allowed the identification and quantification of bioactive compounds of biotechnological importance [5]. Nonetheless, only a limited number of transcriptomes from sea anemones have been sequenced so far [6], [7], [8], [9], [10], [11] Here we performed de novo transcriptome assembly for the sea anemone Anthopleura dowii Verrill (1869) (Actiniaria: Enthemonae: Actinioidea: Actiniidae) by next-generation sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…A 5′-nucleotidase, on the other hand, was identified at low expression levels in the Phalotris mertensi transcriptome, and it was also detected in its venom proteome [57]. Factor Va- and Factor Xa-like proteins are venom serine proteinases distinct from the classical SVSPs [90], and they are believed to have been recruited into the venom proteome on the basis of their occurrences in venoms of the Australian elapid radiation [50].…”
Section: Resultsmentioning
confidence: 99%
“…The precursor of P. mertensi [57] exhibits a Pro-rich insertion in the linker region (detached at the bottom), which includes a BPP-like segment that may generate a BPP after processing.…”
Section: Figurementioning
confidence: 99%
“…There are now a number of snake genome references (Castoe et al, 2013;Vonk et al, 2013;Yin et al, 2016;Perry et al, 2018), and the number of NGS generated venom gland transcriptomes from snakes is also on the rise (Durban et al, 2011;Rokyta et al, 2011Rokyta et al, , 2015Aird et al, 2013;Margres et al, 2013), including for RFS species (McGivern et al, 2014;Zhang et al, 2015;Campos et al, 2016;Pla et al, 2017a,b;Modahl et al, 2018a,b). The sequencing depth of NGS allows for lowly expressed transcripts in snake venom glands that were previously difficult to obtain with expressed sequence tags (ESTs) to now be observed (Campos et al, 2016). In addition to NGS advancements, the increasing sensitivity of mass spectrometry instruments has made it possible to characterize venom proteomes with small amounts of venom (∼100-200 ng).…”
Section: Introductionmentioning
confidence: 99%
“…These more complete venom gland transcriptomes and venom proteomes have revealed common patterns of toxin expression and secretion for RFS (Junqueira- de-Azevedo et al, 2016), as well as identified new venom proteins that had previously not been recognized as venom components in FFS species (OmPraba et al, 2010;Ching et al, 2012;Fry et al, 2012b;Campos et al, 2016). Further, these venoms have been shown to possess toxins with unique activities, such as prey-specific toxicity (Mackessy et al, 2006;Pawlak et al, 2006Pawlak et al, , 2009Heyborne and Mackessy, 2013;Modahl et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%